BEHAVIORAL ALTERATIONS IN OPEN FIELD TEST IN AN EXPERIMENTAL MODEL OF PROSTATITIS - Zubelić, Aleksa; Knežević, Božo; Grubač, Željko; Sutulovic, Nikola; Stanojlović, Olivera; Hrncic, Dragan (Medicinski podmladak, 2019)
Introduction: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is one of the most common diseases of genitourinary system in male population. It is frequently accompanied by psychosocial disorders which include anxiety. Despite numerous clinical studies, the mechanisms of this link are still unclear, partly due to the lack of studies on experimental animal models. Aim: The aim of this study was to examine locomotion activity and anxiety in rats, with experimentally induced CP/CPPS, using the open field test. Material and methods: Wistar male rats were randomly distributed into control and experimental group. In experimental group, CP/CPPS was induced by single intraprostatic injection of 3% λ-carrageenan. Development of pelvic pain syndrome was assessed by evaluating mechanical pain thresholds by electronic Von Frey aesthesiometer (eVF). The rats were individually tested in the open field, seventh day following the intraprostatic injection. Results: In animals from the experimental group, distance and time of ambulatory movement in the open field test were significantly decreased, number of rearing reduced, time spent in the center of the open field significantly decreased, while index of thigmotaxis was significantly increased compared to the control animals. Conclusion: Results of this study indicate anxiogenic effect of CP/CPPS in rats. Keywords: chronic prostatitis, chronic pelvic pain syndrome, open field test, anxiety, rats